Intelectuales y revolución Científicos sociales latinoamericanos en el MIR chileno (1965-1973) - Lozoya López, Ivette (Ariadna Ediciones, 2020)
Role of intellectuals in Latin American political processes, especially in Chile during the 1960s. Intellectual history